La producción social de la ciudad y la emergencia del fideicomiso inmobiliario en los desarrollos urbanos privados : el caso de Canning en la postconvertibilidad - Bertinetti, Agustín Leandro (2021)
In the course of the period defined as post convertibility (2002-2015) an unprecedented demographic and constructive growth can be seen in the city of Canning, south of the suburbs of Buenos Aires. Based on the unique characteristics of urban development in that area, an investment figure emerges in it through which the vast majority of enterprises of the period are built. The present work aims precisely to study the emergence and diffusion of this figure -the real estate trust- in private urban developments in the city of Canning in the period 2002-2015, and the effects on the configuration of the space produced by the development of these ventures through said investment figure.\nThrough it, an attempt is made to show that, due to the advantageous conditions that the city of Canning possesses for private urban development and the favorable economic conditions of the beginning of the period, real estate developers in the area import an investment figure that proves their ability to provide financing and asset security. The versatility that characterizes the trust is related to the adaptability of the real estate sector in the area, from the emerging real estate developers, a powerful social actor that demands the State for its support and accompaniment, both through the generation of infrastructure and equipment conditions in the central corridor as well as the necessary legal and tax regulation of the figure so that it can continue to fulfill its main objective of patrimonial security and financing scenario.\nThe work aims to contribute to the production of scientific knowledge from an approach that will generate relationships between the characteristics of a specific mode of investment in the real estate market and the socio-urban transformations that this form of production in the city allows from urban developments.